Az információs társadalom finn modellje - Móricz, Ádám (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
A new estate of post-industrial societies is being continuously formed in many parts of the world, where creating, conveying, storing and processing information are the basis of almost all social and business interactions. However, a so-called information society could prove to be very different in distinguished countries due to a special social structure, customs, traditions, market conditions and identities of people. Beside Silicon Valley and Singapore, Finland may be handled as a model state of information society as its achieve-ment of combining the new, information-based economy with the previously formed welfare state. In this paper I examine the system of the Finnish information society focusing on its structure and main components (i. e. the state, the adapting society and the information sector), which is followed by a summary of general spatial processes, challenges and regional policy answers as an impact of information society.